Negoziazioni: la natura fra identità e alterità - Roberi, Damiano (Filosofia, 2015)
The present article focuses on the categories of identity and otherness, con- sidered in connection with nature. As nowadays it is no longer possible to consider nature as an invariant (as the target of an aggression perpetrated by humankind or simple non-I), I intend to explore the involvement of nature within the domain of hyperreality (Baudrillard) and hyperobjects, which have led to its disappearance (Morton). These hyper-perspectives share difficulties, which can be summed up in the lack of consideration of the unamendability of the natural world. In order to find a solution to this, the final section of the article stresses the strong need for a new realistic approach to the relationship between history and nature (in light of Bloch and Benjamin). From this perspective, every instant is the locus of a conti- nuous negotiation of the identity and otherness of humankind and nature, a nego- tiation striving to match the complex ecological problems that have overwhelmed us, as well as the ecological fault of human beings.